The mountain's calling - Mabeba, Motlatjo Ahsley (Rhodes University, Faculty of Humanities, School of Languages)
My thesis is a collection of prose "“ in the form of short stories, flash fiction and fragments "“ which explore the silences around living as a queer black South African who has been called to spiritual healing. I draw on lived experiences, dreams, imagination, and my grandmother's folk tales to tell the stories I would love to have read when growing up. In my narratives, queer men navigate different spaces in urban Johannesburg and rural Limpopo. I am inspired by Bettina Judd's words: "Writing is attached to the body"¦ it is my Black woman, queer-identified, round-bodied hand that puts pen to paper, to keyboard, and creates whatever I create." In retelling my grandmother's folk tales with a queer twist, I learn from contemporary fairy tale writers like Kate Bernheimer, Angela Carter and Taisia Kitaiskaia. And in writing about the trauma of rejection by family and community, I am influenced by Bessie Head's A Question of Power.
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; Short stories, South African (English) 21st century; South African fiction (English) 21st century; Homosexuality in literature; Rejection (Psychology) in literature; Spiritual healing in literature; South African essays (English) 21st century; Nigerian fiction (English) History and criticism; English fiction History and criticism; South African fiction (English) History and criticism; Angolan fiction (Portuguese) History and criticism